Trzydzieści srebrników - Kropiwnicki, Jerzy (Annales. Etyka w Życiu Gospodarczym, 2009)
he last 2000 years have seen a change in the prices of silver, grain, land as well as a change in living costs, the salary of hired labourers and police informers. The relationships between those figures have also changed and the monetary systems are quite different nowadays. Thus, it is difficult to answer an apparently simple question: how much is Judas’s 30 pieces of silver? An equivalent of 30 pieces of silver could be 95 zlotys, but also 46 500 zlotys (i.e. about 28 and 13 700 respectively). However, it is obvious that this amount of money is dramatically little in comparison with the scale of betrayal of God and no sum of money would be adequate. But again: even if Judas had lacked faith in Jesus, the sum of money was excessively small for betraying a good and innocent man by one who was chosen by that man from the others and in whom his companions placed so much confidence. Even if Judas had realized that, it was unfortunately too late (Mt. 27: 1–5).